The Relation of Drug Amount, Comorbidity, Blood Pressure, and Residential Area to Drug-Related-Problems of Hypertension Patients (Public Health Perspective Journal, 2020)
Hypertension is a direct cause of various cardiovascular diseases that can cause complications if not controlled. Drug Related Problems (DRPs) are treatment-related problems that can intervene in therapeutic outcomes, one of which is blood pressure. This study analyzed the relationship of factors that influence the case of DRPs in hypertensive patients. This research was an observational quantitative study with a cross-sectional study design conducted by direct interview method to 141 hypertensive prolanis patients in Semarang City Health Center. The instrument used was a questionnaire. The results showed there was a relationship between the number of drugs (p = 0.038), comorbidity (p = 0,000), and blood pressure (p = 0,000) with the case of DRPs. There was no relationship between the area of residence and the case of DRPs (p = 0.569). Multivariate models showed the most influential factors were comorbidity (p = 0,000, OR: 21,689) and blood pressure (p = 0,000, OR: 13,277). The conclusion of this study is comorbidity and blood pressure are the predictors that most influence the case of DRPs in hypertensive patients.